Sandoval leaves behind big legacy - Pappas, Mike (Raton, NM Raton Range, 1990)
Columns written by Mike Pappas, owner of the Sweet Shop Restaurant, for the Raton Daily Range on a wide variety of topics, some historical, some current, some personal.
Newspaper Article by Mike Pappas
Master list item #: 125
File location is in the Raton File Cabinet
Keywords: Sandoval, George; Sandoval, Lillian; George M. Sandoval Memorial Broadcasting Scholarship Fund; KDVR-TV; St. Patrick's School; Life and Customs; Local History; Television Station; Memorial Fund; Public Speaking; Raton, New Mexico; Denver, Colorado; Albuquerque, New Mexico